Avaliação técnica e econômica em sistema de geração de energia elétrica com biogás, fotovoltaico e híbrido biogás fotovoltaico, em aviários de frango de corte - Bissani, Fabiane Mariah (2022)
The current population growth resulted in the resulting increase in the demand for food, reflecting on production systems, altering the industrial and agricultural sectors. Poultry industry, as a branch of food production, has stood out on the national scene in recent decades, bringing with it the discussion of the environmental impacts linked to its activity. Brazil currently has one of the most developed poultry productions in the world, it is a reference when it comes to quality chicken protein. Currently, much of the energy is traded, and obtaining energy has raised concern, as this obtainment is happening in a disorderly and sometimes even irresponsible way, as its obtainment causes several adverse events to the environment being used. Over the years, the search for energy has increased along with population growth. Renewable energies are the indicated options for replacing fossil fuels aiming at generating energy, when compared to other energy sources, they cause a lower environmental impact and reduce the use of petroleum-derived products. In more isolated places, where there is a lack of fossil fuels or even the difficulty of implementing an electric energy distribution network, renewable sources end up being an alternative to supply this energy shortage. Another way to generate energy is photovoltaic cells, which in recent years have stood out for their function of transforming solar energy into electrical energy. These plates can be placed on the roofs of aviaries and can capture the energy emitted by the sun. A well-applied aviary power generation system can generate enough energy for more than half of the property's consumption. However, as these are renewable energy sources, it should be taken into account that some events may occur over time, such as climate change, drop in poultry productivity and maintenance of energy generating systems.